"Tension" on heme by the proximal base and ligand reactivity: conclusions drawn from model compounds for the reaction of hemoglobin. - Sharma, V S (1978)
The kinetic data on model compounds of hemoglobin indicate that in oxyderivatives ligand dissociation rates are sensitive to the "tension" exerted by the proximal base on the metal-to-ligand bond; the corresponding rates for carboxy derivatives are not sensitive to the tension. It is suggested that the metal-to-ligand bond becomes weaker with increased "pull" (or tension) on Fe from the proximal base due to the steric and/or electronic interaction between the ligand, the porphyrin ring, and the proximal base. In model compounds the linear heme Fe-to-CO bound vis-a-vis the bent heme Fe-to-O2 bond probably makes such interactions less significant in carboxy derivatives. It is proposed that the kinetic alpha,beta-chain nonequivalence in Hb4(O2)4 is due to the difference in the tension in the two chains on Fe by the proximal base. The absence of alpha,beta-chain differences large enough to show up in CO dissociation rates from Hb4(CO)4 is explained on the basis of lack of sensitivity of the Fe-CO bound to tension from the proximal base. The implications of the results for the observed cooperative effects in ligand combination (for CO) and dissociation (for O2 and NO) rates of hemoglobin have also been discussed.